Negotiation as a strategy used by the elderly to access Public Health Policies: scoping review protocol (Research, Society and Development, 2021)
Negotiation is an extrajudicial means of conflict resolution that offers cost savings, speed and efficiency in complying with constitutional guarantees such as access to public policies. This review protocol aims to map scientific evidence about what has been produced about negotiation, used by the elderly, for access to public health policies. The proposal will follow the methodological framework of the Joanna Briggs Institute, registered in the Open Science Framework, searches will be carried out in nine indexed sources. Inclusion criteria: original studies referring to elderly people aged 60 years and over who talk about the use of negotiation in accessing public health policies. Studies published in full in national and international journals, with a qualitative and/or quantitative approach, in Portuguese, English and Spanish will be included. There will be no temporal or geographic restriction of the selected publications. Exclusion criteria: texts not available online, editorials, review articles, duplicate articles and those that do not answer the research question defined by the authors.